Model Predictive Control in Multilevel Inverters Part II: Renewable Energies and Grid Applications - Margarita Norambuena; Andres Mora; Cristian Garcia; Jose Rodriguez; Mokhtar Aly; Fernanda Carnielutti; Javier Pereda; Cristian Castillo; Zhenbin Zhang; Venkata Yaramasu; Luca Tarisciotti; Yafei Yin (IEEE Open Journal of Industry Applications)
This article presents the use of model predictive control (MPC) in multilevel inverters for some applications, such as, first, wind generation and, second, photovoltaics, showing that the particular restrictions of each of them can be very easily included in the control algorithm, which is an important advantage of this technique. Another application is in modular multilevel cascaded converters, where it is demonstrated that MPC can operate with very few calculations and fixed switching frequency. The second part of this article is dedicated to comparing MPC with linear control and pulsewidth modulation for multilevel inverters. The main comparison criteria are the switching losses, the distortion in the load current, and the number of commutations. The main conclusion is that MPC is a competitive alternative to linear control for application in multilevel inverters.